"Tree‐in‐bud" opacities with false‐positive Gaffky score and diffuse aspiration bronchiolitis. (16th September 2020) - Mogi, Mizuki; Hori, Hiroshi; Fukuchi, Takahiko; Sugawara, Hitoshi
Abstract : We present a case of diffuse aspiration bronchiolitis (DAB) with a false‐positive Gaffky score. "Tree‐in‐bud" opacities detected after aspiration should be considered DAB rather than mycobacterial infection.